Enhanced ionic conduction in composite polymer electrolytes filled with plant biomass "lignin". Issue 28 (18th March 2022) - Liu, Zitong; Shikinaka, Kazuhiro; Otsuka, Yuichiro; Tominaga, Yoichi
Abstract : A small amount of lignin was used as a filler for composite polymer electrolytes and provided surprisingly improved ion-conductive behavior, exhibiting application potential for flexible batteries with low environmental impact. Abstract : The addition of a small amount of plant biomass-based lignin causes a large improvement in the ionic conductivity of composite polymer electrolytes at room temperature, which can be fabricated easily in a low carbon way for use in future all-solid-state battery applications.